2014
DOI: 10.1128/aem.01638-14
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Bacillus subtilis Strains To Allow Rapid Characterization of Heterologous Diguanylate Cyclases and Phosphodiesterases

Abstract: Microbial processes, including biofilm formation, motility, and virulence, are often regulated by changes in the available concentration of cyclic dimeric guanosine monophosphate (c-di-GMP). Generally, high c-di-GMP concentrations are correlated with decreased motility and increased biofilm formation and low c-di-GMP concentrations are correlated with an increase in motility and activation of virulence pathways. The study of c-di-GMP is complicated, however, by the fact that organisms often encode dozens of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 64 publications
2
32
1
Order By: Relevance
“…c-di-GMP consistently represses flagellum-mediated motility in diverse species, such as P. aeruginosa and B. subtilis, and appears to repress TFP-based twitching motility in P. aeruginosa (20,(77)(78)(79). However, we have found that c-di-GMP promotes TFP-dependent surface motility in C. difficile.…”
Section: Fig 6 Growth On Surfaces Increases Intracellular C-di-gmp Incontrasting
confidence: 45%
See 1 more Smart Citation
“…c-di-GMP consistently represses flagellum-mediated motility in diverse species, such as P. aeruginosa and B. subtilis, and appears to repress TFP-based twitching motility in P. aeruginosa (20,(77)(78)(79). However, we have found that c-di-GMP promotes TFP-dependent surface motility in C. difficile.…”
Section: Fig 6 Growth On Surfaces Increases Intracellular C-di-gmp Incontrasting
confidence: 45%
“…C. difficile 630 encodes a total of 37 predicted diguanylate cyclase (DGC) and phosphodiesterase (PDE) enzymes, which synthesize and degrade, respectively, c-di-GMP (17,18). The catalytic abilities of these enzymes have been independently assessed through heterologous expression in Vibrio cholerae and Bacillus subtilis, which indicated that the majority (21 and 27 enzymes, respectively) are catalytically active (19,20). The remaining proteins may be active in C. difficile or under conditions not tested.…”
mentioning
confidence: 99%
“…The genome of C. difficile 630 codes for 18 predicted DGCs and 19 predicted PDEs, many of which have confirmed enzymatic activity (29,30). Sudarsan et al (26) revealed the presence of a c-di-GMP-I riboswitch, Cd1, upstream of the flgB gene, which is part of one of two loci encoding the flagellum genes in C. difficile.…”
mentioning
confidence: 99%
“…Mutants lacking all enzymes involved in c-di-GMP metabolism have been described (e.g., see references [15][16][17]. A complementary approach involving the use of the constitutive or inducible overexpression of diguanylate cyclases or phosphodiesterase has also been used (e.g., see reference 2).…”
mentioning
confidence: 99%